Picture this: Criminology, image and narrative. (August 2016) - Carrabine, Eamonn
This paper addresses the extent to which the 'narrative turn' in criminology can help inform how images should be read and interpreted. It begins by setting out structuralist analyses of narrative, before discussing an influential art historical approach to iconography and then turns to a substantive analysis of medieval penal imaginaries. Here the argument is that the images of extreme violence did not exactly reflect the realities of medieval life, rather they helped to dramatize them. The implications of this anthropological point are explored in the final section where the relationships between art, discourse and narrative are set out in further detail.